Decidual Stromal Cell Necroptosis Contributes to Polyinosinic-Polycytidylic Acid-Triggered Abnormal Murine Pregnancy - Yu, Shui-Xing; Zhou, Feng-Hua; Chen, Wei; Jiang, Gui-Mei; Du, Chong-Tao; Hu, Gui-Qiu; Liu, Zhen-Zhen; Yan, Shi-Qing; Gu, Jing-Min; Deng, Xu-Ming; Lin, Tong-Jun; Duan, En-Kui; et al. (Frontiers in Immunology, 2017)
Infectious agents can reach the placenta either via the maternal blood or by ascending the genito-urinary tract, and then initially colonizing the maternal decidua. Decidual stromal cells (DSCs) are the major cellular component of the decidua. Although DSCs at the maternal-foetal interface contribute to the regulation of immunity in pregnancy in the face of immunological and physiological challenges, the roles of these DSCs during viral infection remain ill defined. Here, we characterized the response of DSCs to a synthetic double-stranded RNA molecule, poly(I:C), which is a mimic of viral infection. We demonstrated that both transfection of cells with poly(I:C) and addition of extracellular (non-transfected) poly(I:C) trigger the necroptosis of DSCs and that this response is dependent on RLR/IPS-1 signalling and the TLR3/TRIF pathway, respectively. Furthermore, following poly(I:C) challenge, pregnant MLKL-deficient mice had fewer necrotic cells in the mesometrial decidual layer, as well as milder pathological changes in the uterine unit, than did wild-type mice. Collectively, our results establish that necroptosis is a contributing factor in poly(I:C)-triggered abnormal pregnancy and thereby indicate a novel therapeutic strategy for reducing the severity of the adverse effects of viral infections in pregnancy.